Masterpieces of History : The Peaceful End of the Cold War in Europe, 1989 - Zubok, V. M. (Vladislav Martinovich); Blanton, Thomas S.; Savranskaya, Svetlana (Book collections on Project MUSE., 2010)
"This collection presents 122 top-level Soviet, European and American records on the superpowers' role in the annus mirabilis of 1989. This volume offers a rare insider's look at the historic, world-transforming events that culminated in the collapse of communism in Eastern Europe and the end of the Cold War. Complementing the documents are the proceedings of face-to-face mutual interrogation of Russian and American former senior officials from 1998"--[book jacket]